Current sheet axial dynamics of 2.5-kJ KSU-DPF under high-pressure regime - Mohamed, A. E; Abdou, A. E; Ismail, M. I; Lee, S.; Saw, S. H. (IEEE, 2012)
In dense plasma focus (DPF) machines, the high-pressure (HP) regime of operation can be used as alternative technique to short-circuit (SC) test as the current sheet motion is minimal. The SC test was performed to get the right values for the static parameters of the machine. HP shots of more than 30 mbar were performed on the 2.5-kJ Kansas State University DPF machine to determine the deviation of HP values from SC values in computed static inductance and resistance. The test was performed using various gases over a wide range of molecular/atomic mass, starting from hydrogen as the lightest gas up to argon. It was found that the deviation in static inductance and resistance computed from HP method is inversely proportional to gas molecular mass at a certain pressure. The heavy gases like neon and argon were found to give the most accurate results. At 60 mbar of argon, the inductance deviation was 6.5%, and the resistance deviation was 14%. It was found also that increasing gas pressure over 30 mbar using heavy gases like Ar or Ne gives no effective improvement on the computed static impedance. Snowplow model was used to predict the axial position and the axial speed of the current sheet during the HP regime. The model showed that the average axial speed in heavy gases like argon was 0.8 cm/ μs, whereas in hydrogen, it was 1.6 cm/μs.